Bioethanol and biodiesel blended fuels — Feasibility analysis of biofuel feedstocks in Bangladesh. (November 2022) - Mahmud, Shadman; Haider, A.S.M. Redwan; Shahriar, Sk Tahmid; Salehin, Sayedus; Hasan, A.S.M. Monjurul; Johansson, Maria T.
Abstract: In 2019–2020, Bangladesh imported 5.2 million metric tonnes of petroleum products, worth 2.5 billion USD, and 50% of the imports were consumed by the transportation sector. Having limited natural oil reserves and being heavily dependent on oil imports, the country is vulnerable to shocks in the international oil market, which can jeopardize its consistent economic growth. The Government announced a 5% blending of bioethanol with gasoline in 2017, with broken rice, maize, and molasses as the feedstocks, but sourcing biofuel from food crops can hamper the country's food security. This study explores second and third generation feedstocks e.g., organic plants, seeds, agricultural residues, and waste animal fat or skin that can be collected and processed for the extraction of biofuels. Technical potential of biofuel from the feedstocks is analysed which shows that Bangladesh has a potential to extract 44.4 million metric tonnes of bioethanol in a year from agricultural residues with rice residue having the highest potential (71%). Ground nut and rubber seeds can be major feedstocks for biodiesel production having a potential of 61, 000 and 42, 000 metric tonnes per year, respectively. Waste chicken skin can be another promising feedstock for the extraction of biodiesel. Biofuels extracted from these non-edible feedstocks and blended with existing transport fuels can lessen Bangladesh's import bills through a sustainable, environmentally friendly manner. Highlights: 2G and 3G biofuels have potential to reduce Bangladesh's crude oil imports. Among 5 major crops rice residue alone can produce 71% of bioethanol in Bangladesh. Waste chicken skin bears great potential as a third-generation biodiesel feedstock.